2019
DOI: 10.7150/jca.30596
|View full text |Cite
|
Sign up to set email alerts
|

MiR-486-5p inhibits IL-22-induced epithelial-mesenchymal transition of breast cancer cell by repressing Dock1

Abstract: Epithelial-mesenchymal transition (EMT) is one of important steps that lead to cancer metastasis. Interleukin-22 (IL-22) is a T helper 17 (Th17) cells-secreted cytokine, it can promote invasion and metastasis of many cancers. MiR-486-5p is a microRNA that known to function as a tumor suppressor, and bioinformatics analysis predicts that Dock-1 has a binding site of miR-486-5p. In current research, we examined the relative expression levels of miR-486-5p and Dock-1 in 80 pairs of breast cancer tissues and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…The malignant progression of NSCLC is considered to be a comprehensive event that includes a gene expression network and alterations in the tumor microenvironment, in which microRNAs play critical roles [39]. MiR-486-5p, widely documented to be a tumor-suppressive microRNA, inhibits proliferation and invasion in many types of cancers [39,40], In the present study, we observed an interaction between EVI5 and miR-486-5p. To address this question, a dualluciferase reporter assay was performed, and it showed that miR-486-5p significantly inhibited luciferase activity in cells transfected with the wild-type EVI5 3′-UTR, Moreover, overexpression of miR-486-5p prevented EVI5-induced cell proliferation, migration and invasion in NSCLC cells, which further confirms the tumorpromoting function of EVI5 and provides more clues to the regulation network of EVI5.…”
Section: Discussionsupporting
confidence: 60%
“…The malignant progression of NSCLC is considered to be a comprehensive event that includes a gene expression network and alterations in the tumor microenvironment, in which microRNAs play critical roles [39]. MiR-486-5p, widely documented to be a tumor-suppressive microRNA, inhibits proliferation and invasion in many types of cancers [39,40], In the present study, we observed an interaction between EVI5 and miR-486-5p. To address this question, a dualluciferase reporter assay was performed, and it showed that miR-486-5p significantly inhibited luciferase activity in cells transfected with the wild-type EVI5 3′-UTR, Moreover, overexpression of miR-486-5p prevented EVI5-induced cell proliferation, migration and invasion in NSCLC cells, which further confirms the tumorpromoting function of EVI5 and provides more clues to the regulation network of EVI5.…”
Section: Discussionsupporting
confidence: 60%
“…Previous researches have unmasked that miR‐486‐5p elicits a repressive effect on tumor progression. For example, miR‐486‐5p represses Dock1 and inhibits IL‐22‐induced EMT processes 26 . MiR‐486‐5p suppresses non‐small cell lung cancer progression 27 .…”
Section: Discussionmentioning
confidence: 99%
“…By regulating SLC2A1/GLUT1, miR-328 participates in the Warburg effect in COAD (Santasusagna et al, 2018). MiR-486 is related to the molecular mechanisms of several cancers, including cervical cancer (Li et al, 2018a), breast cancer (Li et al, 2019), lung cancer (Tian et al, 2019), esophageal cancer (Lang and Zhao, 2018), ovarian cancer (Ma et al, 2016), and pancreatic cancer (Xia et al, 2019). Kelley et al nearly demonstrated that the expression of miR-486 associates with early-stage of COAD (Kelley et al, 2018).…”
Section: Identification Of Mirna With Prognostic Value In Coadmentioning
confidence: 99%